EFFECT OF AGRICULTURAL PRACTICES ON THE POPULATION OF COLLEMBOLA - MOHAMMAD ILYAS; HINA PARWEZ (The Bioscan, 2011)
Collembola, an important group of soil microarthropods are usually associated with moist habitats. However, some species show adaptation to ecosystems subject to periodic desiccation. This study examined the effect of agricultural practices on the population of Collembola. The population structure of Collembola communities was studied in native agricultural soil at Aligarh along with concomitant changes in a variety of physicochemical factors. Soil apterygotes were dominated by collembolans belonging to the families, Isotomidae and Entomobryoidae. The highest density (44.89%) was of Entomobryoidae found during rainy season followed by Isotomidae (36.74%). However the least population (17.24%) was that 0f Japygidae (Diplura) recorded in spring. The present study establishes a direct effect of high atmospheric temperature and low soil moisture on the population density of these microarthropods and this population is also affected by the soil management practices. These soil microarthropods especially Collembola are of great significance for the health of the soil and its fertility